Study on stress evolution in SiC particles during crack propagation in cast hybrid metal matrix composites using Raman spectroscopy. (June 2015) - Iqbal, AKM Asif; Chen, Songchun; Arai, Yoshio; Araki, Wakako
Highlights: Cracks propagated by the interface debonding and particle fracture. Secondary cracks coalesced with the main crack and final failure occurred. Stress decreased highly with the particle fracture and interfacial debonding. Tensile stresses for interface debonding and particle fracture were estimated. Abstract: The evolution of stress in the SiC particles during crack propagation under monotonic loading in a cast hybrid MMC was investigated by micro Raman spectroscopy. The experiment was carried out in situ in the Raman spectroscopy. Experimental results showed that cracks due to monotonic loading propagated by the debonding of the particle/matrix interface and particle fracture. Secondary cracks those formed in front of the main crack tip coalesced with the main crack in subsequent loading and final failure occurred. A high decrease in stress (several hundreds in MPa) was observed with the interfacial debonding at the interface and with the particle fracture on the particle. Moreover, the critical tensile stresses for particle–matrix interface debonding and particle fracture developed in hybrid MMC were also estimated during the crack propagation.